Jogos digitais e ensino de história antiga : uma abordagem a partir de Assassin`s Creed Odyssey - Tarquino, Paula Katherine (2022)
This text aims to develop an analysis of the digital game Assassin’s Creed Odyssey, in which it presents its narratives in the context of Ancient Greece, during the Peloponnesian War. The game was produced with the support of researchers from classical studies with the aim of making the most believable historical setting possible. Thus, from the discussion of the concepts of historical representation and uses of the past, to understand how the object of study uses historical sources to build its own narrative. In addition, the research seeks to understand how this game can contribute to the teaching of Ancient History in basic education.